Criminal Liability Of School Principals Proven To Have Committed Corruption Of Affirmative Actions From BOS Funds - Tampubolon, Christya Graceilla Putri; Mulyadi, Mahmud; Rizky, Fajar Khaify (Jurnal Mamangan, 2023)
School Operational Assistance Fund (BOS), is a State Budget (APBN) fund given to schools to finance special school needs and must be used and accounted for in accordance with the technical instructions of the BOS fund. One of the cases of corruption of BOS funds based on the Supreme Court Decision Number: 7247 K / Pid.Sus / 2022, which was carried out by the Principal of SMP Dolok Silau, Simalungun Regency, is described as follows: starting in 2019, Harles Sianturi as the Principal was found guilty of committing a criminal act of corruption, which was channeled to finance the provision of learning home access facilities and power and service subscriptions. The purpose of this study is to analyze and determine the formulation of legal regulations regarding affirmative BOS funds and their relationship to state finances. And to analyze and determine the criminal liability of school principals in criminal acts of corruption from affirmative BOS funds in Decision Number 99 / Pid.Sus-Tpk / 2021 / Pn Mdn Jo Decision 8 / Pid.Sus-Tpk / 2022 / Pt Mdn Jo Decision M.A Number: 7247 K / Pid.Sus / 2022. This research method uses a normative juridical research type. Sanctions for deviations and misappropriation of BOS funds can be imposed in accordance with the provisions of laws and regulations, namely: administrative sanctions, personnel sanctions, namely dismissal, demotion, job transfer, application of treasury demands and compensation for BOS funds that are proven to be misused so that they are returned to the education unit or to the state treasury, sanctions against abuse of authority that can harm the state and / or schools and / or students will be imposed by authorized officers / officials.